The case for an HIV cure and how to get there. Issue 1 (January 2021) - Dybul, Mark; Attoye, Timothy; Baptiste, Solange; Cherutich, Peter; Dabis, François; Deeks, Steven G; Dieffenbach, Carl; Doehle, Brian; Goodenow, Maureen M; Jiang, Adam; Kemps, Dominic; Lewin, Sharon R; et al.
Summary: In light of the increasing global burden of new HIV infections, growing financial requirements, and shifting funding landscape, the global health community must accelerate the development and delivery of an HIV cure to complement existing prevention modalities. An effective curative intervention could prevent new infections, overcome the limitations of antiretroviral treatment, combat stigma and discrimination, and provide a sustainable financial solution for pandemic control. We propose steps to plan for an HIV cure now, including defining a target product profile and establishing the HIV Cure Africa Acceleration Partnership (HCAAP), a multidisciplinary public-private partnership that will catalyse and promote HIV cure research through diverse stakeholder engagement. HCAAP will convene stakeholders, including people living with HIV, at an early stage to accelerate the design, social acceptability, and rapid adoption of HIV-cure products.